Nǣothāng patibatngān khrōngkān phāitai phǣn patibatkān Thai khēmkhǣng 2555 (Samākhom Nakbō̜rihān Phatsadu hǣng Prathēt Thai, 2010)
Practical guideline for integrative project under the working plan of Thai strength 2012, Thailand.